The Protection of The Rights of Musyarakah Guarantee Owner Through Judge's Decision - Abdul Halim Muhamad Sholeh (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
In this context, sometimes there is a disparity in decisions between those who ratify the execution of guarantees and auctions only based on the fact that the customer has defaulted by not paying the installments, and there are judges who consider the negligence factor whether it was intentional by the customer or beyond the ability of the customer, so it is the same case namely the existence of a default, but the decision is different due to different interpretations of the concept of negligence in the Indonesian bank regulations or the DSN MUI fatwa. This research is to answer three questions in the study, namely: (1) What is the basis for consideration and legal reasoning by the judges in resolving cases of disputes over the execution of guarantees in musyarakah financing? (2) Why does the decision disparity occur in handling disputes over the execution of guarantees in musyarakah financing? (3) Has the construction of the judge's decision provided protection for the rights of the owner of the guarantee in musyarakah financing? This type of research includes a variety of legal research with a normative juridical study pattern. To answer the problems in the research, the author examines, analyzes and strengthens the argument by using the theory of legal discovery and the theory of justice. The approach used in this research, namely the case approach is used to examine, explore, and examine judge decisions and the philosophical approach is used to explore in depth legal issues regarding the execution of Musyarakah guarantees from various aspects to explain in depth the concept of negligence so as to protect the rights of customers as guarantee owners. The results of this study indicate, firstly, in providing legal considerations and reasoning in the decision on the execution of musyarakah guarantees, the judge based on two different tendencies. Some judges apply legal norms as they are without interpreting and others carry out interdisciplinary interpretations. Second, disparities in decisions arise due to (i) differences in interpreting statutory provisions which give rise to different methods of legal discovery and interpretation (ii) differences in assessing evidence and (iii) differences in the dynamics of thinking due to differences in understanding the meaning of law. Third, the protection of the rights of the guarantee owner in the construction of judge's decisions is still diverse.